2017
DOI: 10.3847/1538-4357/aa7da0
|View full text |Cite
|
Sign up to set email alerts
|

K2 Ultracool Dwarfs Survey. II. The White Light Flare Rate of Young Brown Dwarfs

Abstract: We use Kepler K2 Campaign 4 short-cadence (one-minute) photometry to measure white light flares in the young, moving group brown dwarfs 2MASS J03350208+2342356 (2M0335+23) and 2MASS J03552337+1133437 (2M0355+11), and report on long-cadence (thirty-minute) photometry of a superflare in the Pleiades M8 brown dwarf CFHT-PL-17. The rotation period (5.24 hr) and projected rotational velocity (45 km s −1 ) confirm 2M0335+23 is inflated (R ≥ 0.20R ) as predicted for a 0.06M , 26-Myr old brown dwarf βPic moving group … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 118 publications
(154 reference statements)
1
45
0
Order By: Relevance
“…However, in view of the similarities of the J0331-27 X-ray flare and the X-ray flares on late-M dwarfs described above, we can use the observed optical-to-X-ray energy ratio of LP412-32 (E opt,F ≈ E X,F ) to estimate an optical counterpart of E opt,F 10 33 erg for the X-ray superflare on J0331-27. Remarkably, other white-light superflares observed on L dwarfs (without simultaneous X-ray data) show flare energies of the same order (Jackman et al 2019, Gizis et al 2017. We note that for a flare on an early M dwarf observed simultaneously with XMM-Newton and Kepler (KIC 8454353; see Pizzocaro et al 2019) we also find that the X-ray and optical flare energy are within a factor of two of each other.…”
Section: Discussionsupporting
confidence: 64%
“…However, in view of the similarities of the J0331-27 X-ray flare and the X-ray flares on late-M dwarfs described above, we can use the observed optical-to-X-ray energy ratio of LP412-32 (E opt,F ≈ E X,F ) to estimate an optical counterpart of E opt,F 10 33 erg for the X-ray superflare on J0331-27. Remarkably, other white-light superflares observed on L dwarfs (without simultaneous X-ray data) show flare energies of the same order (Jackman et al 2019, Gizis et al 2017. We note that for a flare on an early M dwarf observed simultaneously with XMM-Newton and Kepler (KIC 8454353; see Pizzocaro et al 2019) we also find that the X-ray and optical flare energy are within a factor of two of each other.…”
Section: Discussionsupporting
confidence: 64%
“…In order to assess the habitability of M dwarf planets, it is important to constrain the flare rates of M dwarfs as a function of their masses and ages. Because of this, we have been studying the flare rates of various mid and late-M dwarfs and early-L dwarfs which were observed by the K2 mission (Howell et al 2014) in various campaigns (see for e.g., Gizis et al 2017b;Paudel et al 2018a). Here we present our results on superflares which we have observed on three late-M dwarfs: 2MASS J08315742+2042213 (hereafter 2M0831+2042), 2MASS J08371832+2050349 (hereafter 2M0837+2050) and 2MASS J08312608+2244586 (hereafter 2M0831+2244).…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopy of an L5 dwarf by Liebert et al (2003) showed an Hα flare, although this event lacked the continuum enhancement associated with white light flares. Observations of an L5 dwarf (Gizis et al 2017b) not sensitive to late spectral types, this requirement limits observations to a small number of nearby early L dwarfs. Wide-field surveys (e.g.…”
Section: Introductionmentioning
confidence: 99%